2010
DOI: 10.4103/0256-4947.65253
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes of diabetic women: Charting Oman’s progress towards the goals of the Saint Vincent Declaration

Abstract: BACKGROUND AND OBJECTIVES:Oman provides comprehensive care for the detection and management of diabetes during pregnancy with the goal of reducing or eliminating adverse outcomes for mothers and newborns. We assessed the outcome of pregnancies complicated with diabetes as compared to healthy controls.SUBJECTS AND METHODS:A 1-year retrospective review of registry records was conducted on pregnant women with gestational diabetes mellitus (GDM) and pre-gestational diabetes mellitus (PGDM). Of the 5394 women regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
5
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 13 publications
5
32
5
2
Order By: Relevance
“…Although our estimated risks for maternal, fetal, and neonatal complications of pre-GDM and GDM are similar to other studies [21, 23, 25, 26, 32], the impact on the Saudi pregnant population is expected to be bigger due to the high burden of these conditions in the community, which calls for immediate, evidence-based measures including the following:Preconception care should be integrated in the healthcare of Saudi diabetic women considering the proven effects associated with such services in reducing all the complications of pre-GDM [9]. …”
Section: Implication To Practicesupporting
confidence: 89%
“…Although our estimated risks for maternal, fetal, and neonatal complications of pre-GDM and GDM are similar to other studies [21, 23, 25, 26, 32], the impact on the Saudi pregnant population is expected to be bigger due to the high burden of these conditions in the community, which calls for immediate, evidence-based measures including the following:Preconception care should be integrated in the healthcare of Saudi diabetic women considering the proven effects associated with such services in reducing all the complications of pre-GDM [9]. …”
Section: Implication To Practicesupporting
confidence: 89%
“…The total number of women diagnosed to have GDM in this study was 23/307(7.49 %) and this is certainly more than what was reported by Barkat et al, i.e., prevalence rate is 4.17% in Omani pregnant women [5]. This may be due to continuous changes in the diagnostic criteria for GDM and changes in life style, as we found that Omani pregnant women are generally obese whether they are at risk or not of developing GDM.…”
Section: Discussioncontrasting
confidence: 48%
“…The reported prevalence of DM in Oman is about 12 % and equally affects males and females; about 4 % of pregnant women in Oman develop GDM by the time of delivery [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…This noticeable rise in the prevalence of PDM during pregnancy could be explained in part by the improved screening and detection of diabetes, however the main cause in our opinion is the increased prevalence of T2DM among adults in the Saudi population to an estimated range of 21to 23% [14]. It is worth noting that the prevalence of 3.7% for PDM is very high compared to other regions of the world [6,15-17]. …”
Section: Discussionmentioning
confidence: 99%